Figurative Language Used in Bible Old Testament - Ronsmin, Felisita; Putu Cahyani Putri Utami, Ni (Pustaka : Jurnal Ilmu-Ilmu Budaya; Vol 23 No 1 (2023)DO - 10.24843/PJIIB.2023.v23.i01.p10, 2023)
This article aimed to analyze the figurative language used in the Bible Old Testament. The objectives of this research are to find out types of figurative language and the meanings in the Bible Old Testament. To analyze the data, the author uses the main theory proposed by Knickerbocker and Reninger (1963) entitled Interpreting Literature and the theory of meaning proposed by Leech (1981) entitled Semantics. This article analyzed the data by using a qualitative method. The data were collected by reading the Bible, taking note and classifying the sentences that contain figurative language. The data was taken from the Bible Old Testament. The types of figurative language found in Bible Old Testament were simile (3 items or 37,5%), metaphor (1 item or 12,5%), personification (1 item or 12,5%), paradox (1 item or 12,5%), and hyperbole (2 items or 25%). Simile is the dominant type and there are 3 types with the least result found in the Bible Old Testament namely metaphor, personification, and paradox.